Factors Affecting Student Absenteeism in Rural Elementary Schools of Kalahandi District of Odisha - Sagar, Deeptimayee; Nayak, Prasanta Kumar (Voices of Teachers and Teacher Educators, 2026)
This study attempts to understand student absenteeism by exploring its related factors in rural elementary schools of migration-prone Golamunda block in Kalahandi district. The study also aims to assess the measures taken by the stakeholders to address this issue. A mixed-method approach with an explanatory-sequential design was followed. The students, parents, teachers, and headmasters of elementary schools constituted the population of the study. Cluster and purposive sampling techniques were followed for the quantitative and qualitative phase of data collection respectively. Student enrolment and retention data sheets, structured and semi-structured interview schedules were used as the tools for data collection. The quantitative data were analyzed through frequency and percentage analysis, while the qualitative data were sorted, coded, categorised and analyzed thematically. After analyzing the data, four overarching themes were generated. They were weak economic condition of families, lack of aspiration towards education and career among students, casual attitude of parents towards children’s education, and inadequate community participation. By incorporating the perspectives of various stakeholders, attempts were made to comprehend the nuances of absenteeism that can help parents, educators, educational administrators, and policymakers to gain a deeper understanding of the nature of absenteeism. Proper planning and interventions would result in better school attendance, retention, adjustment, and high educational achievements of students.